Identifikasi berbasis karakter molekuler Nucleopolyhedrovirus pada larva Helicoverpa armigera Hubner (Lepidoptera: Noctuidae) asal Bogor, Jawa Barat - R. Yayi Munara Kusumah; Trendy Hartanto; Fitrianingrum Kurniawati (Jurnal Entomologi Indonesia, 2022)
Nucleopolyhedrovirus (NPV) is a potential biological control agent recommended to control corn cob borer larvae (Helicoverpa armigera Huber). NPV characters can be studied using various detection and identification methods. One technique to study the character of NPV is polymerase chain reaction (PCR) followed by analysis of the results of nucleotide and amino acid sequences. The molecular character of NPV in infected H. armigera larvae in corn plantations in Cibeureum Village, Dramaga District, Bogor Regency using DNA polymerase partial gene sequences needs to be done. The methods used to study the character of the NPV consisted of DNA isolation using a modified CTAB method, partial gene amplification of DNA polymerase using HearNPVF1 and HearNPVR1, and analysis of the level of homology of nucleotide and amino acid sequences compared to other countries and phylogeny. PCR amplification using specific primers was successfully carried out with the HearNPV DNA polymerase partial gene DNA band measuring about 1,200 bp. Phylogenetic analysis was also successfully carried out and showed that there was a high relationship between HearNPV isolates from Indonesia (Bogor, West Java) and NPV isolates that infect Helicoverpa from other countries such as: Spain, Australia, the Netherlands, India, Brazil, Russia, and China with nucleotide and amino acid homology values ​​of 99%. HearNPV isolates from Bogor were in the same group as NPVs that attacked the Genus Helicoverpa from other countries, while NPVs from other genera were in separate groups based on phylogenetic analysis using Mega 7 software.